Examining the spatiotemporal dynamics of urban heat island and its impact on air pollution in Thailand - Veeranun Songsom; Pawarit Jaruk; Thongchai Suteerasak (Environmental Challenges)
Bangkok's, the capital of Thailand, rapid economic growth has led to a rising population and vehicle use, intensifying urban heat island (UHI) effects and air pollution. The relationship between UHI and air pollutants remains uncertain, influenced by factors such as location, spatial distribution, and the type of pollutants. Additionally, seasonality may contribute to this uncertainty, as UHI, land surface temperature, and air pollutants follow seasonal patterns. Understanding not only the relationship but also the trends in UHI and air pollution is crucial for gaining valuable insights that can help predict future scenarios and inform effective management and policy decisions. This study investigates the association between UHI and air pollution using data from the Sentinel-5P, which does not provide a single pollutant but instead offers measurements for nitrogen dioxide (NO2), sulfur dioxide (SO2), ozone (O3), carbon monoxide (CO), formaldehyde (HCHO), and aerosol optical depth (AOD) from Terra MODIS. Rainfall and normalized difference vegetation index (NDVI) are incorporated to analyze the factors influencing air pollution. Smoothed daytime and nighttime land surface temperatures (LST) from MODIS are converted to UHI in Bangkok Metropolitan and Vicinity from 2019 to 2023 by calculating the difference between LST and averaged LST within rural area. Their correlation (Pearson's correlation coefficient) with air pollutants and trend analysis is demonstrated using data from individual location. The relationship analysis is divided into four cases: all data, winter, dry, and rainy seasons. The results indicated all air pollutants peak from winter to the dry season, corresponding to the agricultural burning period, except for O3, which peaks during the rainy season. The impact of UHI-pollutants correlations is evident, with NO2 levels peaking during the dry season in the daytime and AOD, CO, and HCHO levels peaking during the winter season at nighttime. Additionally, trend analysis revealed an increasing pattern in daytime UHI as well as in NO and SO2 levels, highlighting the potential intensification of urban heat and associated air pollution over time. The influence of NDVI remains inconclusive aligned with seasonal. We outline strategies to mitigate UHI and air pollution based on our findings. This research highlights the urgent need for international collaboration to reduce air pollution caused by burning activities.